Exploring the Ayurvedic Concepts for Reproductive Tract Infections - Nawal, Priyanka; Neelima, A (International Research Journal of Ayurveda & Yoga, 2024)
In the wider dimension of prevalence of RTIs throughout the globe, and lack of effective, safe and economic management, the need for exploring alternative medical systems was increasingly emphasized. A concept research was conducted to investigate Ayurvedic concepts for RTIs using comparative literature from Ayurveda and modern medicine.The results show a fair ground to understand the factors undergoing RTIs and throw a great promise to integrate the Ayurvedic concepts with the ongoing interventionist strategies to address RTIs effectively.